Determination of Phenol Components in Rachis and Leaves of Some Grape Varieties (Vitis vinifera L.) - Jamea, F. F.; Al-Kaisey, M.T.; Al-Maliky, Z. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Total phenols, Proanthocyanidin, Catechin  and Epicatechin wrer extracted and determined in ten rachis and leaves of grape  varieties (Vitis vinifera L.) namely: Shadda Soudda, Rush Meo, Rossi 5, Kamali, Halawani, Black Monica, Dase Al-Anz,  Buhrizi, Rossi 7 and Thompson. through two seasons. The results indicated that the rachis of the tested varieties contain total phenol in concentration (2079.76 and 2557.59), (1458.18 and 2119.89), (2233.01 and 3322.26), (3106.22 and 4613.43), (3251.15 and 4739.05), (1668.88 and 2548.59) and (4163.11 and 6202.90). (3922.22 and 5848.17), (3359.03 and 4915.36) and (1035.45 and 1502.27) mg/kg for the tow seasons, respectively. The rachis of  the white grape varieties contain the higher phenolic components. The rachis of the tested varieties were variable in Proanthocyanidin, Catechin  and Epicatechin content.  The total phenol, Proanthocyanidin, Catechin  and Epicatechin of leaves were determined in all tested grape varieties. The full expanded leaf was rich in phenolic compounds in comperisan with maturity stage. The results shows the grape leaves contain higher total phenolic components, Proanthocyanidin, Catechin  and Epicatechin in comparison with the rachis of all tested varieties